2016
DOI: 10.1017/s0954422415000153
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion regulation in childhood obesity: implications for prevention and treatment

Abstract: Stress and negative emotions pose a major threat to public health, by increasing the risk of obesity. Since the management process for emotions (emotion regulation; ER) is developed in childhood, we present a novel conceptual framework model for the role of ER in the prevention and treatment of childhood obesity. A narrative review of the literature by electronic database search (MEDLINE, Web of Knowledge and Scopus) was conducted of observational and interventional/experimental literature on ER and obesity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 164 publications
(197 reference statements)
1
103
2
4
Order By: Relevance
“…Emotion regulation plays a central role in obesity. 137 In toddlers, poor emotion regulation skills prospectively predict higher BMI, even after controlling for baseline BMI and behavioral problems. 138 This relationship may be explained by emotional eating to cope with negative emotions.…”
Section: Early Life Adversity and Emotion Regulationmentioning
confidence: 96%
“…Emotion regulation plays a central role in obesity. 137 In toddlers, poor emotion regulation skills prospectively predict higher BMI, even after controlling for baseline BMI and behavioral problems. 138 This relationship may be explained by emotional eating to cope with negative emotions.…”
Section: Early Life Adversity and Emotion Regulationmentioning
confidence: 96%
“…From a public health perspective, stressful events are difficult to avoid, but the prevention of a chronic physiological stress reaction might be beneficial in maintaining optimal metabolic health. One such opportunity is by incorporating education on stress management and emotion regulation in prevention programmes and in school curricula (Aparicio, Canals, Arija, De Henauw, & Michels, ). After all, good stress and emotion coping might prevent chronic cortisol increases and stress‐related behaviours such as emotional eating.…”
Section: Conclusion and Translational Potentialmentioning
confidence: 99%
“…1: emotional distress) [37,70,86]. Emotional distress is associated with psychopathology [39,83,97], medical diseases [125,127,129], and obesity [8,42,58,79,101,123].…”
Section: Stress Conceptualizationmentioning
confidence: 99%
“…Childhood obesity: growing prevalence, multiple consequences, and modest treatment success Recent prevalence rates collected by the World Health Organization [150] revealed that, worldwide, 18% of the school-aged children and adolescents (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) are diagnosed with overweight and 8% with obesity. These prevalence rates have tripled since 1975, demonstrating the growing problem of pediatric overweight and obesity [150].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation